The impact of Covid-19 pandemic on counter-terrorism in Indonesia - Machya Astuti Dewi,; Iva Rachmawati, (Penerbit Universiti Kebangsaan Malaysia, 2024)
There is an assumption that the COVID-19 pandemic will reduce the number of acts of terrorism. However, that opinion has yet to be proven in Indonesia. Acts of terrorism continue to grow despite the COVID-19 pandemic limiting human activities. Various acts of terror, both physical and non-physical, through social media occur. Even the campaign of terrorism through cyberspace is increasingly massive and difficult to contain. This phenomenon is interesting to study, significantly how Indonesia’s COVID-19 pandemic impacts counter-terrorism measures. To answer this question, data through internet searches on counter-terrorism programs from the National Agency for Counter-terrorism in Indonesia and related institutions are explored. Researchers also interviewed officials from the National Counter-terrorism Agency and former terrorism offenders. The results showed that the COVID-19 pandemic affected Indonesia’s counter-terrorism strategy. First, the campaign of terrorist groups that are rife in the mass media is addressed by counter-narrative through social media. Second, there has been a shift in counter-terrorism efforts from a hard approach to a soft approach. Third, there is increasing Pentahelix synergy in countering terrorism in Indonesia.